2013
DOI: 10.5897/ajfs2013.1067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fruit quality traits of traditional varieties of tomato (Solanum lycopersicum) grown in Tunisia

Abstract: Physicochemical, nutritional, agronomic and sensorial parameters, which define fruit quality of tomato (Solanum lycopersicum), were evaluated in 13 traditional varieties collected from several localities in Tunisia, using three commercial varieties as controls. Several varieties were identified as better score for total solid, soluble solid, sugars/acid ratio and vitamin C concentration than the commercial varieties. These varieties could be a resource of good quality in breeding programmes. The correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 16 publications
6
15
1
1
Order By: Relevance
“…The pH found are in line with those obtained by Fagbohoun and Kiki [16] and Dossou et al [15] who found values from 3.7 to 4.1 and 4.01 to 4.17 respectively. In contrary, these values are lower than those obtained by Aoun et al [24] who reported values between 4.19 and 4.45 for 16 tomato varieties collected from Tunisia. Previous studies reported that pH of 3 to 6 is very favorable to the growth of yeasts and molds while bacteria prefer neutral media, typically pH between 7 and 9 [25].…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…The pH found are in line with those obtained by Fagbohoun and Kiki [16] and Dossou et al [15] who found values from 3.7 to 4.1 and 4.01 to 4.17 respectively. In contrary, these values are lower than those obtained by Aoun et al [24] who reported values between 4.19 and 4.45 for 16 tomato varieties collected from Tunisia. Previous studies reported that pH of 3 to 6 is very favorable to the growth of yeasts and molds while bacteria prefer neutral media, typically pH between 7 and 9 [25].…”
Section: Resultscontrasting
confidence: 55%
“…The degree brix ranged from 4.07 to 5.50 with a significant difference among the three sampling sites. The degree brix obtained for this variety is superior to that found by Aoun et al [24] who reported values ranging from 2.02 to 4.57 for 16 varieties of traditional tomatoes from Tunisia. The values found were similar to those found by Fagbohoun and Kiki [16] who reported values ranging from 4.2 to 5.1.…”
Section: Resultsmentioning
confidence: 46%
“…Salunkhe et al (1974) and Moneruzzaman et al (2008) reported the increase of soluble solids content with the tomatoes ripening and maturation, because of the polysaccharide biosynthesis or degradation. The amount of soluble solids of the four studied cultivars ranged from 3.4 °Brix for 'Argeș 11' to 4.8 °Brix for 'Ștefănești 22', being comparable with the results obtained by Aoun et al (2013) and Duma (2015), who reported in different tomato cultivars values between 2.02 and 4.57 °Brix and between 4.6 and 6.3 °Brix, respectively. When comparing the soluble solids content among the assessed cultivars, only small variation can be observed, the highest and statistical significant difference being obtained in 'Ștefănești 22'.…”
Section: Resultssupporting
confidence: 78%
“…Organic acids, lipids, minerals and pigments are the remaining soluble solids besides a very small quantity of sucrose. The total solids of tomatoes consist also of insoluble solids (ISS) (25%) which include proteins, cellulose, hemicellulose, pectins and polysaccharides, which determine fruit juice (Aoun et al, 2013). Salunkhe et al (1974) and Moneruzzaman et al (2008) reported the increase of soluble solids content with the tomatoes ripening and maturation, because of the polysaccharide biosynthesis or degradation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation